Capital Punishment for Drug Abuse Crime: Legal Limitations and Requirements - Bayu, Faryzuhud (Law Research Review Quarterly, 2021)
I write this paper about the death penalty for narcotics dealers, many countries still apply the death penalty like one of them is Indonesia, although many criticize the execution of capital punishment for drug dealers, but the death penalty is still done in Indonesia, because it is believed to be the most appropriate step for the drug dealers who have damaged this generation of Indonesian nation, and in this paper I justify or approve if the drug dealer is sentenced to death because the drugs damage the young generation and damage the nation's morale.